2014
DOI: 10.1111/tpj.12568
|View full text |Cite
|
Sign up to set email alerts
|

A pair of homoeolog ClpP5 genes underlies a virescent yellow‐like mutant and its modifier in maize

Abstract: SUMMARYGene-background interaction is a commonly observed phenomenon in many species, but the molecular mechanisms of such an interaction is less well understood. Here we report the cloning of a maize mutant gene and its modifier. A recessive mutant with a virescent yellow-like (vyl) phenotype was identified in an ethyl methanesulfonate-mutagenized population derived from the maize inbred line B73. Homozygous mutant maize plants exhibited a yellow leaf phenotype after emergence but gradually recovered and beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Natural high light shining upon pale leaves in spring led to a more extreme pale phenotype, whereas reduced light intensity through shading resulted in the rapid greening of leaf color of ‘YJX’. Similar light dependent leaf phenotypic changes have been reported previously in maize and Arabidopsis3435. Our data revealed that the non-shaded pale leaves of ‘YJX’ contained aberrant chloroplasts with undeveloped thylakoid membranes and significantly reduced chlorophylls and total carotenoids, both of which play crucial roles in photosystem assembly and, light-harvesting and the latter in photo-protection in chloroplasts3637, were found in PL compared to SL of ‘YJX’.…”
Section: Discussionsupporting
confidence: 88%
“…Natural high light shining upon pale leaves in spring led to a more extreme pale phenotype, whereas reduced light intensity through shading resulted in the rapid greening of leaf color of ‘YJX’. Similar light dependent leaf phenotypic changes have been reported previously in maize and Arabidopsis3435. Our data revealed that the non-shaded pale leaves of ‘YJX’ contained aberrant chloroplasts with undeveloped thylakoid membranes and significantly reduced chlorophylls and total carotenoids, both of which play crucial roles in photosystem assembly and, light-harvesting and the latter in photo-protection in chloroplasts3637, were found in PL compared to SL of ‘YJX’.…”
Section: Discussionsupporting
confidence: 88%
“…Chlorophyll a was reduced more than chlorophyll b (Table 1). The malfunctioning chloroplast and reduced chlorophyll biosynthesis in yellow young leaves seem to be a common feature for many temperature-dependent virescent mutants such as those found in Arabidopsis [20], cotton [32]; rice [7,18,26,33,34,35,36,37,38], maize [39], wheat [40], and apple [41]. Biswal et al [42] showed that the biosynthesis of chlorophyll a is closely linked to chloroplast development.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes function in chlorophyll biosynthesis and catabolism, or in the developmental regulation of chloroplast, in the metabolism of carotenoids [26,33,34,35,36]. In Arabidopsis [44], rice [36], and maize [39], several virescent mutants were due to nucleotide changes in the chloroplast Clp protease complex which play important roles in plastid development.…”
Section: Discussionmentioning
confidence: 99%
“…The PML collection was assembled as a tool to deeply sample the 133 complement of nuclear genes required for the biogenesis of photosyn-134 thetically competent chloroplasts in plants. The collection consists of 135 2000 independently arising mutants that were selected from Mu- 136 active maize lines based on seedling chlorophyll deficiency (pale 137 green, albino, yellow, virescent, etc.) or an hcf phenotype.…”
mentioning
confidence: 99%